Studi Komparatif Implementasi Model Pembelajaran STAD (Student Team Achievement Divisions) dan Model Pembelajaran Konvensional pada Materi Fikih di Madrasah Ibtidaiyah - Ardina Maharani; Mukh Nursikin (Journal of Innovative and Creativity, 2025)
This study aims to examine and compare the effectiveness of the STAD (Student Team Achievement Divisions) cooperative learning model with the conventional learning model on student learning outcomes in Fiqh material at Madrasah Ibtidaiyah (MI). Low PAI learning outcomes are often caused by conventional teacher-centered methods, which make students passive. Therefore, there is a need for innovative learning models that can increase student participation. This study uses a literature review method by analyzing various secondary data sources, such as scientific journal articles, books, and research reports published in the last five years. The collected data were analyzed qualitatively using content and comparative analysis techniques. The results of the literature review show that the STAD (Student Team Achievement Divisions) learning model is significantly more effective in improving student learning outcomes than conventional models. The application of STAD (Student Team Achievement Divisions) has been proven to be able to foster motivation, learning activities, and student collaboration through teamwork, individual quizzes, and team recognition. In addition, this model also contributes to the formation of positive character traits, such as responsibility and cooperation. Based on these findings, it is concluded that the STAD (Student Team Achievement Divisions) model is a superior alternative for teaching Fiqh in MI, encouraging the creation of a more interactive and student-centered learning environment.